Research on Power Transmission Capability of VSC-HVDC Based on Second Order LADRC. (February 2019) - Zhang, Fang; Chen, Xiaokai; Zhang, Yanxia; Jiang, Huilan
Abstract: Voltage source converter based high voltage direct current (VSC-HVDC) technology is considered one of the most desirable technique for massive renewable power integration, for which converter controller design and power transmission capacity research are two essential topic. A novel VSC-HVDC converter station controller is proposed based on second order linear active disturbance rejection control (LADRC), which realizes rapid and independent adjustment of active and reactive power. The controller take full advantage of ADRC to improve dynamic response and to strengthen robustness as well as disturbance rejection ability of the system. A small signal model of overall system including AC system dynamics is established. Based on eigenvalue analysis, power transmission limit of VSC-VHDC is investigated on the perspective of global stability of the whole system. The influence of control strategy and reactive control mode on VSC power transmission capacity are then analyzed respectively. Examples are given to verify the results obtained by small signal stability analysis. The research in the paper provides theoretical support for the application of LADRC in VSC-HVDC domain.